Stereotactic Body Radiation Therapy as Salvage for Intrathoracic Recurrence in Patients With Previously Irradiated Locally Advanced Non–Small Cell Lung Cancer. (April 2016) - Parks, Jason; Kloecker, Goetz; Woo, Shiao; Dunlap, Neal E.
Abstract : Introduction: The purpose of this study is to provide data on the outcomes of using stereotactic body radiotherapy (SBRT) as a means of salvage for non–small cell lung cancer (NSCLC) relapses previously treated with radiation. Materials and Methods: The records of 128 consecutive patients treated with thoracic SBRT from 2009 through 2012 were retrospectively reviewed. Twenty-seven patients (29 lesions) treated with prior thoracic radiation for stage IIB-IIIB NSCLC with subsequent recurrences and retreated with SBRT were identified. Results: The median prior radiation dose was 64.8 Gy (range, 45 to 74 Gy) with a median retreatment dose of 50 Gy (range, 30 to 54 Gy), corresponding to a biological equivalent dose of 100 Gy (range, 48 to 151 Gy), at a median time of 13.4 months from prior radiation. The mean follow-up after salvage SBRT was 22 months. Local failure following salvage was 11%, nodal failure was 37%, and distant failure was 30%. The local recurrence-free survival at 2 years was 72%. Out-of-field failure was predictive for worse local control (hazard ratio, 47.38; 95% confidence interval, 5.795-64.899). Progression-free survival at 1 year was 55% and 38% at 2 years. Overall survival at 2 years from SBRT salvage was 79%. Salvage biological equivalent dose ≥100 Gy was predictive of improved progression-free survival (48% vs. 18%, P =0.021) and overall survival (91% vs. 52%, P =0.004) at 2 years. The rate of symptomatic pneumonitis was 63% and chest wall pain reported was 26%. Conclusions: We observed improved outcomes following SBRT as a means of salvage for locally advanced recurrent NSCLC over traditional radiation therapy options. The toxicities were greater than expected from naive lung irradiation, but the adverse effects remained controlled with medications.